2006
DOI: 10.1080/00207450500341522
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Obesity by Acupuncture

Abstract: The present study is an investigation of the results of the studies on the effects of acupuncture application therapy on obesity. It has been reported that acupuncture application in obesity treatment is effective in procuring weight loss. It can affect appetite, intestinal motility, and metabolism, as well as emotional factors such as stress. Increases in neural activity in the ventromedial nuclei of the hypothalamus, in tone in the smooth muscle of the stomach and in levels of enkephalin, beta endorphin, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…Further, researches show that the application of acupuncture can cause increases in neural activity associated with the ventromedial nuclei of the hypothalamus, the tone of the smooth muscle of the stomach, and levels of enkephalin, b-endorphin and serotonin in plasma and brain tissue. 8,9 Despite the above results, the effectiveness of acupuncture on obesity has not been fully understood. Lacey et al 10 reviewed seven randomized controlled trials (RCTs) and reported a modest positive effect of acupuncture for weight loss, although his review was nonsystematic.…”
Section: Introductionmentioning
confidence: 99%
“…Further, researches show that the application of acupuncture can cause increases in neural activity associated with the ventromedial nuclei of the hypothalamus, the tone of the smooth muscle of the stomach, and levels of enkephalin, b-endorphin and serotonin in plasma and brain tissue. 8,9 Despite the above results, the effectiveness of acupuncture on obesity has not been fully understood. Lacey et al 10 reviewed seven randomized controlled trials (RCTs) and reported a modest positive effect of acupuncture for weight loss, although his review was nonsystematic.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these effects, it is thought that the increase in plasma levels of β-endorphin after acupuncture application can contribute to the body weight loss in obese people by mobilizing the body energy depots through lipolytic effect. [9][10][11][12][13][14] Using this paradigm, obesity and/or excess appetite has been conceptualized in a variety of ways, such as "heat" in the stomach and intestine, a deficiency of qi in the spleen and stomach, or a deficiency of primary qi. 1 Based on this beliefs about the causes of obesity, a variety of acupoints is targeted in the treatment of obesity, including Neiguan (P6), Fenglong (St40), Liangmen (St 21), Guanyuan (R4), Zusanli (St36), Tianshu (St25), and Quchi (LI11), where P refers to a pericardium, St to stomach, R to Ren, and LI to large intestine meridians.…”
Section: Introductionmentioning
confidence: 99%
“…So zeigen einige Studien, dass Akupunktur zur Reduktion von Übergewicht beitragen kann, mögli-cherweise durch eine Erhöhung des Leptin-und des Endorphinspiegels [26,27]. Ausserdem wirkt Akupunktur unterstützend bei der Raucherentwöh-nung [28] und kann Stress oder dessen Auswirkungen vermindern [29].…”
Section: Akupunktur Und Triggerpunktbehandlungunclassified